Asiatic fern Cyrtomium fortunei J. Sm. (Dryopteridaceae) – a new naturalized fern in the flora of Slovenia - Nejc Jogan; Azra Šabić; Urban Šilc (Natura Sloveniae)
A naturalized population of Asiatic fern Cyrtomium fortunei J. Sm. was found in the surroundings of Nova Gorica. It is the first record of the species in the country, although the locality is an expected prolongation of the secondary distribution range with the species’ concentration in southern foothills of the Carnic Prealps (N Italy). The locality is characterized by mild temperate submediterranean climate and slightly degraded forest vegetation of the alliance Carpinion orientalis, where the fern occurs in the herb layer. Local occurrence of the fern represents the easternmost point of its secondary distribution range in Northeastern Italy, although this could possibly be connected with the immediate vicinity of the graveyards at the top of the slope.